EYE MOVEMENT PATTERNS IN WEB-BASED TASKS: THE INFLUENCE OF TARGET POSITION, INDIVIDUAL POSITIONING, AND TASK TYPE ON VISUAL INFORMATION PROCESSING (Update) - José Vasconcelos-Raposo (PsychTech & Health Journal)
This paper is a conceptual and interpretative update of a previously published version. The main objective of this study was to understand how target position influences eye movements in navigational and informative tasks. The sample comprised 20 university students (13 females 7 males, aged 18-44). Participants completed a socio-demographic questionnaire and performed two tasks: navigational and informative. Eye movements were recorded during task performance. A 2x2 MANOVA was conducted to analyze linear combinations of dependent variables (blink duration, blink frequency, and fixation duration) across task types and target positions. Results revealed significant differences in eye movement patterns between tasks. The navigational task showed shorter average blink durations (204.236-1656.397 ms) and fewer blinks (1.987-9.786) compared to the informative task (553.598-1864.440 ms; 9.648-20.040 blinks, respectively). Strong interaction effects were observed between average fixation duration and individual position in both navigational (ηp2 = .216) and informative (ηp2 = .176) tasks. We conclude that target position in the navigational task significantly influences university students’ eye movements, while individual position affects eye movements in both navigational and informative tasks. These findings contribute to understanding how task demands modulate visual attention and potentially affect user interface design and educational technology.